Afforestation of Lateritic Pans of Goa - a Case Study - Kumar, Shashi; Bisht, N. S.; Rao, R. N. (Indian Forester, 1995)
A study was conducted to grow Acacia auriculiformis on lateritic pans. By utilising the mine dumps. The best results were obtained on pit cum mine dump plantation. The study can be useful for the reclamation of lateritic pans as well as for the rehabilitation of the mine rejects.